1991
DOI: 10.2337/diab.40.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Archaeology of NIDDM: Excavation of the “Thrifty” Genotype

Abstract: Since the 1940s, numerous cases of non-insulin-dependent diabetes mellitus (NIDDM) have been observed in certain American Indian populations. Extremely high prevalence rates of NIDDM occur most strikingly in several tribes of Paleo-Indians, whose ancestors migrated to North America greater than 11,000 yr ago. Archaeological evidence from that period indicates that certain groups of Paleo-Indians maintained an arctic-like hunter-gatherer life-style in an area in temperate North America ranging from Wyoming to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 0 publications
0
23
0
1
Order By: Relevance
“…Yet, in contemporary societies, as food is usually available in unlimited amounts and life is sedentary, thrifty genes become deleterious, as they increase susceptibility to diabetes mellitus. [1][2][3][4]37 This hypothesis has been widely supported by epidemiological, [11][12][13] genetic and evolutionary researches. 4,14,15 In particular, some specific genes have been identified or considered as 'thrifty genes' (or 'thrifty SNP'), including calpain-10 gene and G-proteincoupled receptor 35 gene, 4 APOE*4 allele, 14 SNPs in FABP2, MTP, b3AR (the Trp64Arg SNP), apo-E, UCP2, UCP3-p, PPARg2, LEPR, adiponectin and so on.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Yet, in contemporary societies, as food is usually available in unlimited amounts and life is sedentary, thrifty genes become deleterious, as they increase susceptibility to diabetes mellitus. [1][2][3][4]37 This hypothesis has been widely supported by epidemiological, [11][12][13] genetic and evolutionary researches. 4,14,15 In particular, some specific genes have been identified or considered as 'thrifty genes' (or 'thrifty SNP'), including calpain-10 gene and G-proteincoupled receptor 35 gene, 4 APOE*4 allele, 14 SNPs in FABP2, MTP, b3AR (the Trp64Arg SNP), apo-E, UCP2, UCP3-p, PPARg2, LEPR, adiponectin and so on.…”
Section: Discussionmentioning
confidence: 88%
“…However, in contemporary societies, as food is usually available in unlimited amounts, the 'thrifty genotype' no longer provides a survival advantage, but renders its owners more susceptible to obesity and diabetes. 5 Although variants of this hypothesis have formed the topic of vigorous debate, [6][7][8][9][10] there are many researches that tend to support this hypothesis, not only in epidemiology [11][12][13] but also in population genetics or evolutionary ecology. 4,14,15 One of the problems of using the 'thrifty gene' concept is that most individuals associate it with a metabolic trait related to a frugal utilization of fuel, which indeed was Neel's (1962) first intention.…”
Section: Introductionmentioning
confidence: 99%
“…With the sustained availability of food this protective mechanism became deleterious leading The 'carnivore connection' S Colagiuri and J Brand Miller to an increase in type 2 diabetes (Neel, 1962(Neel, ,1992. Subsequently others have suggested that insulin resistance is the phenotypic expression of the thrifty gene (Wendorf & Goldfine, 1991;O'Dea, 1991). On the other hand, Hales and Barker have proposed the 'thrifty phenotype' hypothesis which invokes maternal and infant malnourishment to explain the increase in modern day diseases (Hales & Barker, 1992).…”
Section: The Evolution Of Insulin Resistance and Hyperinsulinaemiamentioning
confidence: 99%
“…La recuperación ocurre primero en los músculos que fueron últimamente afectados, en un periodo de tiempo entre 3 a 72 horas (2). El compromiso de motoneurona superior y de músculos respiratorios es raro, pero puede ser fatal (24). Hay hiporreflexia o arreflexia paradójica en un paciente que muestra signos de hipertiroidismo.…”
Section: Discussionunclassified